2021
DOI: 10.1002/mrd.23550
|View full text |Cite
|
Sign up to set email alerts
|

Oviduct epithelial cells‐derived extracellular vesicles improve preimplantation developmental competence of in vitro produced porcine parthenogenetic and cloned embryos

Abstract: Extracellular vesicles (EVs) carry bioactive cargoes involved in the early preimplantation development. This study investigated the effects of EVs obtained from an oviductal epithelial cell (OEC) conditioned medium on the developmental competence of in parthenogenetic activation (PA) and somatic cell nuclear transfer (SCNT) porcine embryos. The OEC‐EV‐treated group showed significant increases in blastocyst formation and hatching rates compared to the control group (40.8% ± 2.2% and 20.1% ± 2.1% vs. 24.9% ± 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Similarly, Fang et al [ 56 ] reported that oEV obtained from in vitro oviductal epithelial cell-conditioned media improved the development competence of parthenogenetic and somatic nuclear transfer porcine embryos. In contrast to our results, supplementation for 7 days provided better blastocyst rates than compared to three days with in vitro obtained oEVs.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, Fang et al [ 56 ] reported that oEV obtained from in vitro oviductal epithelial cell-conditioned media improved the development competence of parthenogenetic and somatic nuclear transfer porcine embryos. In contrast to our results, supplementation for 7 days provided better blastocyst rates than compared to three days with in vitro obtained oEVs.…”
Section: Discussionmentioning
confidence: 96%
“…The enhanced embryo development, survival, and the downregulation of SIRT1 in EVs-treated embryos suggests the possibility of a post-transcriptional downregulation of SIRT1 in EV-treated embryos by miRNAs [ 83 ]. In this way, SIRT1 in embryos could be potentially targeted by miR-21-5p or miR-9-5p present in bovine oEVs and in porcine oEVs [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. In the present study, although SIRT1 was not ...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oviduct is the site of zygote birth as well as preembryonic development. Current research indicates that O-EVs can improve embryo blastocyst formation rate, embryo survival rate, embryo hatching rate, and post-embryo transfer birth rate ( Almiñana et al, 2017 ; Qu et al, 2019 ; Fang et al, 2022b ; de Alcântara-Neto et al, 2022 ). Furthermore, O-EVs can improve embryo development after cryopreservation and survival rate after vitrification ( Lopera-Vasquez et al, 2017 ; Leal et al, 2022 ; Sidrat et al, 2022 ).…”
Section: Extracellular Vesicles’ Clinical Utility In Assisted Reprodu...mentioning
confidence: 99%
“…In vitro generation of porcine parthenogenetic embryos. Electric parthenogenetic activation of in vitro matured porcine oocytes was used to generate porcine embryos as showed in previous reports 16,17,28 . Briefly, ovaries were collected from a local slaughterhouse in Daejeon city, and cumulus-oocyte complexes (COCs) were aspirated.…”
mentioning
confidence: 99%